Kresy (Polish Eastern Borderlands) in Polish Literature of 1918–2018. Significant Interpretative Perspectives - Uliasz, Stanisław (Tematy i Konteksty, 2021)
The paper offers a comprehensive, synthetic account of the discourse on the subject of the Polish Eastern Borderland over the course of the last hundred years. It analyses the ways in which the understanding of the notion of Kresy and “borderland”, as well as the strategies for presenting the term, have changed, including attempts to replace this category with other terms. Furthermore, the paper characterises the dynamics concerning the transformations of situational contexts that emerged in the period of the Second Polish Republic, developed during World War II, after 1945 (in the country and abroad) and continuing from the 1980s and1990s to the present. Significant interpretative perspectives include, among others, the trends in literary schools, the legends and myths of the Polish Eastern Borderland, the notion of the borderline of cultures, small homelands, and methodological phrases and breakthroughs (spatial turn, geopoetics, postcolonial criticism).